Is the voluntary control of exercise in man necessary for the ventilatory response? - Adams, L (1984)
The ventilatory response to electrically induced exercise (EEL) was studied in eighteen normal subjects and compared with the response to performing the same exercise voluntarily (EV). EEL was produced by surface electrode stimulation of the quadriceps and hamstring muscles so as to cause a pushing movement at 1 HZ against a spring load; this produced no pain or discomfort. Matching of EV to EEL was achieved by subjects copying a tension signal recorded during EEL and displayed on a storage oscilloscope. There were no differences between the resting states measured before either form of exercise. The ventilatory response (change in ventilation as a ratio of the change in CO2 elimination) was similar in the two types of exercise. The increases in ventilation and CO2 elimination were greater with EEL. Small but significant increases in the gas exchange ratio and serum lactate were found for EEL but not for EV, suggesting an increase in anaerobic metabolism in EEL. End-tidal PCO2 showed little change in either form of exercise. In some runs end-tidal PCO2 rose, but insufficiently to account for the ventilatory response as judged by the response to inhaled CO2. In two subjects arterial blood samples showed small and inconsistent changes in both Pa,CO2 and PaO2 for EV and EEL. pH and base excess changes also were consistent with more anaerobiosis with EEL compared to EV. The first ten breaths of exercise were used to study the on transient. In EV, expiratory duration shortened and ventilation increased significantly on the first breath but CO2 elimination did not increase until the second breath; in EEL, these variables did not change significantly until the second breath. For the remainder of the on transient the pattern of the ventilatory response was similar for EV and EEL. By the end of the on transient both EV and EEL had reached approximately 80% of their final steady-state values. These results suggest that a normal ventilatory response can occur in the absence of a drive to exercise from the cortex.